KELUARGA BERENCANA (KB) DALAM PERSPEKTIF MAQASHID SYARIAH - Mahmudin Hasibuan; Akhir Saleh Pulungan, Nur Hakima Akhirani Nasution, Mhd Romadhoni (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This research aims to find out the basis of Islamic law in family planning programs. And to find out about the Family Planning (KB) program in the study of maqashid sharia. This research was carried out using library research and paying attention to the field (Field Research). Literature study is a process of searching for various literature, study results related to the research to be conducted. Literature study can be likened to a key that will open everything that can help solve research problems. The results of the research show that the legal basis for the Family Planning (KB) program is the generality of the verses which indicate that it is permissible to follow the family planning (KB) program, such as Surah al-Baqarah verse 233, Surah Luqman verse 14, Surah an-Nisa verse 9. In verse al- Baqarah verse 233, explains that children must be breastfed for two full years, therefore it is hoped that the mother will not become pregnant again before the baby is two and a half years old or in other words, the child's birth should be spaced at least thirty months, so that the child can be healthy and protected from disease, because of milk. The mother is the best for the baby's growth. This indicates the importance of the Family Planning program in realizing these desires. and in Surah an-Nisa verse 9 it is stated that economic weakness, lack of stable physical health conditions, and children's intellectual weakness due to lack of nutritious food, are the responsibility of both parents. And another legal basis is qiyas to 'azl, because both are human endeavors or efforts to regulate birth. And the ulama who allow this family planning program are Imam al-Ghazali, Imam Ramli, Shaykh al-Hariri, Shaykh Syalthut, for the reason of maintaining the mother's health, avoiding maternal difficulties, and spacing children apart. The Family Planning (KB) program in the study of maqashid sharia is (1) hifdzul nasl, because it benefits the health or education of children if the child's birth distance is too close. Even protection against the harm (bad effects) of family planning must take priority over taking advantage of the benefits of family planning itself. And with a small family size, it will be easier to achieve family prosperity and happiness, especially regarding maternal and child health. (2) Hifdzul nafs, because it benefits the life safety or health of the mother. (3) din, because there is a mafsadat of narrowing livelihoods.